Quantifying emergency department admission rates for people with a learning disability. Issue 9 (8th April 2011) - Williamson, Tim; Flowers, Joanne; Cooke, Matthew
Abstract : No data is routinely collected by emergency departments (ED) in the UK to identify people who attend and who have a learning disability. This group have numerous additional needs in their healthcare management and a lack of support could be detrimental to their care. F800 codes from the International Classification of Diseases (ICD-10) that identify disorders of psychological development are often used to categorise specific disorders once admitted to hospital. Consequently, the F800 codes of patients who were admitted to hospital from Birmingham Heartlands Hospital ED for 1 year have been analysed to obtain some of this data. This study argues that, although only a small proportion of the admissions from this ED were by people with an F800 code, the exact numbers of attendances in many EDs remain unknown and the impact of their disabilities on their immediate care and the workload of the ED medical staff may be significant.